Coincidence Doppler shift lifetime measurements in 73,74Se and 74Br using the EUROBALL Cluster cube array - Loritz, Rainer; Iordanov, O.; Galindo, E.; Jungclaus, A.; Kast, D.; Lieb, K.P.; Teich, C.; Cristancho, F.; Ender, Ch.; Härtlein, T.; Köck, Frank; Schwalm, Dirk (The European physical journal. A, Hadrons and nuclei, 1999)
Subpicosecond lifetimes of high spin states in the rotational nuclei 73Se, 74Se and 74Br have been measured using the 58Ni +19F compound reaction and the Doppler Shift Attenuation method. Six EUROBALL Cluster detectors arranged in cube geometry allowed us to select the relevant transitions in γγ coincidence mode. The high counting statistics achieved in this setup also facilitated the determination of average sidefeeding times, which were found to agree rather well with the results of Monte-Carlo calculations of the particle and γ-ray evaporation process. The deduced quadrupole strengths and deformations are compared with the results of previous measurements and the predictions of Cranked Shell Model calculations. In 74Br, a large and constant prolate deformation of β2= 0.37(1) was found for the presumed 4+ and 3− two-quasiparticle bands.